Bipolar Affective Disorder: Severe Episodes of Depression Now with Psychotic Symptoms Accompanied by Threshold Type Personality Disorder and Suicide Attempts - Muthia Dinillah, Naila (Jurnal sosial dan sains, 2025)
Introduction: Bipolar disorder is a psychiatric disorder that falls into the category of mood disorders. Personality disorder is a pattern of inner experience and behavior that deviates from culture, and is pervasive and inflexible. Individuals with Body Dysmorphic Disorder have a significant increase in the likelihood of developing depression According to WHO, patients with borderline personality disorder are estimated to have about 73% of patients will have about 3 suicide attempts in their lifetime, while patients with bipolar disorder have a higher risk of suicide compared to the general population Case report: This paper includes a case analysis of an 18-year-old boy who was in the middle of a experiencing self-injurious behavior accompanied by depressive symptoms, and suicide attempts. The patient's history of significant emotional trauma, including bullying, and family conflicts. Patients show symptoms in people with BPD, such as impulsive behavior, identity crisis, and extreme mood swings. The diagnosis in patients is that there is bipolar affective disorder, episodes of severe depression with psychotic symptoms accompanied by borderline type personality disorder and suicide attempts, then there are problems in the primary support group (family) and the Global Assessment of Functional (GAF) Scale of patients 20-11. Manajemen yang diberikan pada pasien ini adalah kombinasi farmakoterapi berupa Escitalopram dan Aripriprazole. Serta pasien diberikan terapi perilaku kognitif (cognitive behavioral therapy). Conclusion: The case of bipolar affective disorder is a mood disorder characterized by depressive and manic or hypomanic episodes. The patient in this case was experiencing bipolar affective disorder with a major depressive episode with psychotic symptoms. In patients, there is a disorder on axis II, which is in the form of a threshold type personality. Borderline personality disorder (BPD) involves significant affective lability and carries a great risk for depression. Threshold type disorder, characterized by emotional instability, impulsivity and depressive disorders such as depressive affect, loss of interest and lack of energy so that it is easy to get tired. Based on suicide risk factors, patients have experienced physical and sexual abuse, patients are also victims of bullying and patients have conflicts in the family. The management provided is in the form of a combination of pharmacotherapy, such as antipsychotics and antidepressants to reduce depressive and psychotic symptoms, as well as cognitive-behavioral therapy.